2017
DOI: 10.1111/jth.13619
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of PLDN (pallidin) is a mechanism for platelet dense granule deficiency in RUNX1 haplodeficiency

Abstract: Summary Background Inherited RUNX1 haplodeficiency is associated with thrombocytopenia and platelet dysfunction. Dense granule (DG) deficiency is reported in patients with RUNX1 haplodeficiency, but the molecular mechanisms are unknown. Platelet mRNA expression profiling in a patient previously reported by us with a RUNX1 mutation and platelet dysfunction showed decreased expression of PLDN (BLOC1S6), which encodes for pallidin, a subunit of BLOC-1 (biogenesis of lysosome-related organelles complex-1) involve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 31 publications
(78 reference statements)
0
24
0
Order By: Relevance
“…Moreover, our expression profiling studies in the same patient showed that a wide array of genes involved in platelet function and formation are downregulated [8]. We have shown that several relevant genes including PRKQ [9] , MYL9 [10], ALOX12 [12], PLDN [24] and PCTP [25] are direct transcriptional targets of RUNX1. Thus, we postulate that the secretory abnormalities result from aberrations in common pathways critical to the general process of exocytosis, for example, involving vesicle transport mechanisms, Rab proteins, and SNARE proteins [16, 26].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, our expression profiling studies in the same patient showed that a wide array of genes involved in platelet function and formation are downregulated [8]. We have shown that several relevant genes including PRKQ [9] , MYL9 [10], ALOX12 [12], PLDN [24] and PCTP [25] are direct transcriptional targets of RUNX1. Thus, we postulate that the secretory abnormalities result from aberrations in common pathways critical to the general process of exocytosis, for example, involving vesicle transport mechanisms, Rab proteins, and SNARE proteins [16, 26].…”
Section: Discussionmentioning
confidence: 99%
“…44 Two preliminary studies reported that the genes encoding RAB1B (RAB1B), a low molecular weight GTPase that is essential for vesicle transport between the endoplasmic reticulum and the Golgi apparatus, and Pallidin (PLDN), which is involved in granule vesicle biogenesis, were both downregulated in RUNX1 haplodeficiency, and shown to be direct targets for RUNX1 regulation, providing possible mechanisms for the defective granule biogenesis and secretion observed in RUNX1 deficiency. 45,46…”
Section: Explaining the Platelet Disorders Caused By Runx1 Defectsmentioning
confidence: 99%
“…26 PLDN encodes for pallidin, a protein that is involved in biogenesis of dense granules and is decreased in the pallid mouse and the human Hermansky-Pudlak syndrome. 2729 There is also evidence that patients with RUNX1 mutations may have global defects that compromise agonist-stimulated secretion of contents of the α- and dense-granules, as well as from the acid hydrolase containing vesicles, which is unrelated to a deficiency in the granule contents.…”
Section: Runx1mentioning
confidence: 99%
“…In our platelet transcript profiling studies of a patient with RUNX1 mutation numerous genes relevant to multiple platelet biological pathways were downregulated. 33 Several genes have been shown to be direct transcriptional targets of RUNX1, including 12-lipoxygenase ( ALOX12 ), 25 platelet factor 4 ( PF4 ), 34 platelet myosin light chain ( MYL9 ), 35 protein kinase C-θ ( PRKCQ ), 36 palladin ( PLDN ), 26 and the thrombopoietin receptor ( c-MPL ). 37 These impact various aspects of MK biology, platelet production, structure, signaling, and responses.…”
Section: Runx1mentioning
confidence: 99%